AHNAK2 Participates in the Stress‐Induced Nonclassical FGF1 Secretion Pathway. Issue 8 (August 2015) - Kirov, Aleksandr; Kacer, Doreen; Conley, Barbara A.; Vary, Calvin P.H.; Prudovsky, Igor
ABSTRACT FGF1 is a nonclassically released growth factor that regulates carcinogenesis, angiogenesis, and inflammation. In vitro and in vivo, FGF1 export is stimulated by cell stress. Upon stress, FGF1 is transported to the plasma membrane where it localizes prior to transmembrane translocation. To determine which proteins participate in the submembrane localization of FGF1 and its export, we used immunoprecipitation mass spectrometry to identify novel proteins that associate with FGF1 during heat shock. The heat shock‐dependent association of FGF1 with the large protein AHNAK2 was observed. Heat shock induced the translocation of FGF1 and AHNAK2 to the cytoskeletal fraction. In heat‐shocked cells, FGF1 and the C‐terminal fragment of AHNAK2 colocalized with F‐actin in the vicinity of the cell membrane. Depletion of AHNAK2 resulted in a drastic decrease of stress‐induced FGF1 export but did not affect spontaneous FGF2 export and FGF1 release induced by the inhibition of Notch signaling. Thus, AHNAK2 is an important element of the FGF1 nonclassical export pathway. J. Cell. Biochem. 116: 1522–1531, 2015. © 2015 Wiley Periodicals, Inc.